Implementasi Projek Penguatan Profil Pelajar Pancasila dan Profil Pelajar Rahmatan Lil Alamin (P5PPRA) di Madrasah Tsanawiyah - Selly Dwi Cahyani; Muhammad Isnaini; Halimatussakdiah (PAI RAFAH, 2025)
This study examines the implementation of the Pancasila Student Profile and Rahmatan Lil Alamin Student Profile (P5PPRA) project at MTsN 1 Ogan Ilir for grade VII, including the supporting and inhibiting factors. A qualitative descriptive approach with a field study design was applied. Informants consisted of the head of the madrasah, the curriculum coordinator, the P5PPRA project leader, and three students. Data was collected through observation, interviews, and documentation, with analysis involving data reduction, presentation, and conclusion drawing. The results show that the P5PPRA implementation includes planning, execution, and evaluation. Planning involves forming a project team, assessing madrasa readiness, choosing dimensions, themes, and time allocation, developing project modules, and creating reporting strategies. Implementation occurs through students’ activities, while evaluation is conducted by assessing project achievements. Supporting factors include various stakeholders’ support, facilities, student motivation, and budget. Inhibiting factors involve high administrative burdens, teachers' lack of understanding of P5PPRA, and differences in student abilities.